2022
DOI: 10.21037/jtd-22-82
|View full text |Cite
|
Sign up to set email alerts
|

MiR-223-3p affects myocardial inflammation and apoptosis following myocardial infarction via targeting FBXW7

Abstract: Background: Myocardial infarction (MI) is one of the main causes of disability and death in the world, leading to myocarditis and cardiomyocyte apoptosis. Studies have shown that microRNA (miRNA) is involved in myocarditis and apoptosis. The main purpose of this study was to explore the regulatory mechanism of miR-223-3p on myocarditis and apoptosis after MI. Methods: We cultured H9c2 cells and detected the expression of miR-223-3p in cells treated with different concentrations of H 2 O 2 . Sprague Dawley (SD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…As a highly and specifically expressed miRNA in platelets, 28,46 miR-223-3p is involved in many pathological processes. 12,47 Besides ACSL3, Twist1, 48 TGFBR2, 48 FBXW7, 49 and SPI1 50 were also suppressed by miR-223-3p in cardiomyocytes. In our study, we did not examine the effect of platelet internalization on other functions of cardiomyocytes, but we do not rule out the possibility that increased miR-223-3p is also involved in arrhythmia 3 as well as cell necroptosis 51 and apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…As a highly and specifically expressed miRNA in platelets, 28,46 miR-223-3p is involved in many pathological processes. 12,47 Besides ACSL3, Twist1, 48 TGFBR2, 48 FBXW7, 49 and SPI1 50 were also suppressed by miR-223-3p in cardiomyocytes. In our study, we did not examine the effect of platelet internalization on other functions of cardiomyocytes, but we do not rule out the possibility that increased miR-223-3p is also involved in arrhythmia 3 as well as cell necroptosis 51 and apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…FBXW7 is a F-box WD40 protein and serves as a substrate recognition subunit of the SCF (SKP1/CUL1/F-box protein) E3 ubiquitin ligase complex. In recent years, a lot of work has found that miR-223-3p targets FBXW7 to regulate myocardial inflammation and apoptosis after myocardial infarction [ 18 ]. Additionally, miR322 modulates the FBXW7/notch pathway to affect cardioprotection against IR injury [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has uncovered that FBXW7 expression was elevated in myocardial IR injury. Inhibition of FBXW7 significantly alleviated inflammatory response, cell apoptosis, and IR-induced myocardial injury in mice [ 18 , 19 ]. Thus, we speculated that DLX6-AS1 may alleviate myocardial IR injury by regulating miR-204-5p/FBXW7 axis.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have shown deleterious effects of increased miR-223, including enhancement of fibrosis [19] and stimulation of atherogenesis [20]. In contrast, other authors reported beneficial effects of elevated miR-223 expression, including protection against ischemia-reperfusion injury [21,22] and apoptosis, as well as myocarditis [23]. In a murine model, miR-223 ameliorated fibrosis, inflammation and apoptosis, and mediated angiogenesis [24].…”
Section: Discussionmentioning
confidence: 99%